(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Heat electricity at the stations external environment temperature rise with station power relatively decreased goes him in moderation holding stand up problem very complicated task is considered Him in moderation holding stand up many to factors depend on This is the problem solution to do for heat electricity stations about has been very a lot information analysis to do Demand will be done. In the article external environment temperature change with absorption cooling of the car the work mode power and a steam turbine power change between dependence temperature , cooling coefficient, cooling of the car energetic useful the work coefficient and from the station use coefficient and another sizes based on analysis done